Analysis Of Factors Influencing Health Workers Implementing Hand Hygiene At Peulumat Community Health Center, South Aceh - Sry Rizki; Nurromsyah Nasution; Asmima Yanti (International Journal of Health and Social Behavior, 2024)
Nurses' compliance in carrying out hand hygiene is very important because infection and disease transmission can be caused by health workers who are not compliant in carrying out hand hygiene every time they carry out health service actions. Health workers' compliance in carrying out hand hygiene both before and after carrying out procedures for providing health services can be a problem that must be considered due to various factors that are closely related to compliance in carrying it out. This research was conducted to analyze factors related to health workers' compliance in implementing hand hygiene at the Peulumat Health Center, South Aceh. The design used is descriptive correlation with a cross sectional approach. The total sample was 80 health workers. Data was obtained by interview using a questionnaire. There is an influence on attitudes with results (p 0.003) and length of service (p 0.002) the availability of hand hygiene facilities (p 0.000) which influences the compliance of health workers in implementing hand hygiene at the Peulumat Health Center in South Aceh. Based on statistical tests, it was found that factors that can influence the health of workers in carrying out hand hygiene consist of attitude, length of service, availability of facilities for carrying out hand hygiene. The implication for recommended services is that supervision and motivation of health workers need to be increased to carry out hand hygiene in accordance with recommendations. The research implication is that it is hoped that there will be research with a larger sample size, involving other people as researchers and using video.